Characterization of cylindrical and strip-shaped tamoxifen citrate-loaded biodegradable implants - Hiremath, Jagadeesh G; Patel, Pragnesh B; Aitha, Rajesh Kumar; Mura, Prasanthkumar; G, Subhash Palavalli (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to prepare tamoxifen citrate (TC)-loaded cylindrical and strip-shaped polymeric subdermal implants. The implant was based on poly(Îµ-caprolactone), a low-melting, biodegradable and biocompatible polymer. Polyethylene glycol (PEG 4000) was used to enhance solubility and release of the drug in the phosphate buffer saline pH 7.4. Implants were prepared by a standardized melt manufacturing method. The prepared implants were evaluated for their physicochemical parameters and drug content in implants by UV spectrophotometric method. PCL-based implants were characterized by Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry, X-ray diffraction studies(XRD) and scanning electron microscopy (SEM). DSC studies showed that the TC in the implants was in the amorphous state. In vitro drug release studies were performed in methanol:phosphate-buffered saline (pH 7.4) at 37Â±2Â°C by using horizontal water bath shaker. Stability study was carried out for 90 days, there was no significant change in drug content and other parameters of the PCL-based formulations.